1996
DOI: 10.1021/bi953077m
|View full text |Cite
|
Sign up to set email alerts
|

Human Erythrocyte Sugar Transport is Incompatible with Available Carrier Models

Abstract: GLUT1-mediated, passive D-glucose transport in human erythrocytes is asymmetric, Vmax and K(m)(app) for D-glucose uptake at 4 degrees C are 10-fold lower than Vmax and K(m)(app) for D-glucose export. Transport asymmetry is not observed for GLUT1-mediated 3-O-methylglucose transport in rat, rabbit, and avian erythrocytes and rat adipocytes where Vmax for sugar uptake and exit are identical. This suggests that transport asymmetry is either an intrinsic catalytic property of human GLUT1 or that factors present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
107
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(110 citation statements)
references
References 52 publications
3
107
0
Order By: Relevance
“…A similar analysis of tracer kinetic data reported also a millimolar K,, in rat brain (Cunningham et a!., 1986), but a different study suggested that analyzing brain glucose content as a function of plasma glucose content using the standard model gave a K~of 14 mM in rat brain (Mason et a!., i992). Such a high K, can be taken as an indication of an almost linear brain-blood glucose relationship.Some studies have suggested that although the human GLUT-i has anomalous asymmetric kinetic propefties, most mammalian erythrocyte kinetics are symmetric (Cloherty et al, 1996). Nevertheless, we show in Appendix that the linear relationship between brain and plasma glucose levels using reversible MichaelisMenten kinetics is preserved even when assuming asymmetric kinetic properties.…”
mentioning
confidence: 67%
“…A similar analysis of tracer kinetic data reported also a millimolar K,, in rat brain (Cunningham et a!., 1986), but a different study suggested that analyzing brain glucose content as a function of plasma glucose content using the standard model gave a K~of 14 mM in rat brain (Mason et a!., i992). Such a high K, can be taken as an indication of an almost linear brain-blood glucose relationship.Some studies have suggested that although the human GLUT-i has anomalous asymmetric kinetic propefties, most mammalian erythrocyte kinetics are symmetric (Cloherty et al, 1996). Nevertheless, we show in Appendix that the linear relationship between brain and plasma glucose levels using reversible MichaelisMenten kinetics is preserved even when assuming asymmetric kinetic properties.…”
mentioning
confidence: 67%
“…However, these transporters catalyze bi-directional fluxes, and the presence of intracellular and/or extracellular glucose alters the kinetics of transport both in and out of the cell. This bidirectional transport must be actively considered when modeling the flow of glucose from blood to the individual types of neural cells, primarily neurons and glial cells (see below Blomqvist et al, 1991;Carruthers, 1990;Choi et al, 2001;Cloherty et al, 1996;de Graaf et al, 2001; Gjedde, 1980; Gruetter et al, 1998; Hebert and Carruthers, 1991;Qutub and Hunt, 2005).The capacity for glucose transport depends on the concentration of the transporter proteins as well as their intrinsic catalytic turnover activity or number of transport cycles catalyzed per transporter per sec (k cat ) within the respective cellular compartments. It is relatively easy to determine the total concentration of GLUTs in brain microvessels, as these vessels can be readily isolated from whole brain (Vannucci, 1994).…”
mentioning
confidence: 99%
“…Transport measurements in red cell ghosts show that the rate of net cellular export of 10 mmol/L glucose into saline containing 3 mmol/L glucose is inhibited 50% by intracellular ATP (i.e., when transport is asymmetric). Thus red cells serve as less efficient glucose carriers when metabolically replete, but efficiently transfer intracellular glucose to surrounding tissues when demand for glycolytic ATP is increased (Carruthers, 1986, Cloherty et al, 1996 Heard et al, 2000).Although not yet specifically shown, this may apply to other GLUT1-expressing cells, such as BBB endothelial cells and astrocytes. Glucose transporter1 transport asymmetry in erythrocytes declines from 12-fold at 41C to 4-fold at 241C to 1.3-fold at 371C (Lowe and Walmsley, 1986).…”
mentioning
confidence: 99%
“…This new model of transport via GLUT1 built on previous transport, structural, and modeling studies (1,2,3,7,10,20,22,(23)(24)(25)(26)(27)(28) delineates how glucose and quercetin may slide via a pore structure and is clearly differentiated from the conventional alternating carrier description of glucose transport. It offers an explanation for the widely dispersed mutation sites affecting GLUT1-DS (30,31).…”
mentioning
confidence: 99%